Comparison of adverse events between intensity-modulated radiation therapy and tomotherapy for early stage breast cancer: a retrospective cohort study - Xia, Yan; Yang, Yan-Cheng; Ren, Hang-Qi; Wang, Yan-Zun; Li, Qing-Feng; Yu, Ya-Yuan; Yang, Guang-Ran; Li, Yang-ke; Jin, Kai-Cheng; Luo, Qi-Fa; Bian, Zhi-Heng; Zeng, Tian; et al. (Frontiers in Oncology, 2025)
IntroductionEarly stage breast cancer treated with adjuvant radiotherapy with two different techniques, tomotherapy (TOMO) and intensity-modulated radiation therapy (IMRT), and their acute adverse events in terms of skin toxicity, localized edema, sore throat, tracheal mucositis, nausea, oral mucositis, esophagitis, and pneumonitis outcomes are compared.Materials/methodsA retrospective cohort study was conducted to compare the adverse events of IMRT and TOMO in early stage breast cancer. We reviewed the data of female patients who underwent lumpectomy or mastectomy for breast cancer at the Oncology Department of the First Affiliated Hospital, Army Medical University, from September 2021 to February 2024. A total of 315 female patients were enrolled in this study, including 130 and 185 in the TOMO and IMRT groups, respectively. In this study, the adverse events in the two groups of patients were compared and analyzed.ResultsThe median age of the patients in this retrospective cohort was 47 years (range, 20–74 years). The follow-up period was 3 months. A total of 185 patients (59%) received IMRT and 130 (41%) underwent TOMO. No significant differences were observed in terms of menopausal status, laterality, pathology, estrogen receptor status, progesterone receptor status, triple negative, clinical T stage, clinical N stage, or surgical methods. Negative HER-2 overexpression was found in 38% and 51% of the TOMO and IMRT groups, respectively (relative risk [RR], 0.63; 95% CI 0.40 –0.99; P = 0.053).With regard to the degree of tumor differentiation, poor- moderate differentiation was 69% in the TOMO group and 81% in the IMRT group (RR 0.53; 95% CI, 0.31 –0.89; P = 0.052). In the TOMO and IMRT groups, 66% and 55% of the patients received hormone therapy, respectively (RR 1.59; 95% CI 1.00 –2.53; P = 0.5). However, there were no statistical differences in the demographic and tumor characteristics between the TOMO and IMRT groups. A comparison of adverse events between the TOMO and IMRT groups showed no significant differences in localized edema, sore throat, tracheal mucositis, nausea, oral mucositis, and the IMRT groups. Compared to the IMRT group, the TOMO group had a higher proportion of grade 3–4 skin toxicity [16.2% (TOMO) versus 7.6% (IMRT), (RR 2.13; 95% CI 1.04 –4.37; P = 0.017)]. Pneumonitis was lower in the TOMO group than in the IMRT group [0.0% (TOMO) versus 4.3% (IMRT), (RR 1.05; 95% CI 1.01 –1.08; P = 0.016].ConclusionsCompared with IMRT, TOMO decreases the incidence of radiation pneumonitis but fails to improve acute skin toxicity. Based on our research, TOMO may contribute to higher odds of acute skin toxicity, which should be considered by clinicians.